Respostas

2014-03-16T18:40:26-03:00
Basta calcular f(5) e (-2).
f(5) = 5² - 4.5 - 2
f(5) = 25 - 20 - 2
f(5) = 3

f(-2) = (-2)² - 4.(-2) - 2
f(-2) = 4 + 8 - 2
f(-2) = 10

f(5) -3.f(-2)
3 -3.10 = 
= -27  
2014-03-16T18:47:11-03:00
Sendo f(x)= x2 - 4x - 2
f(5) - 3.f(-2) = ?
 
É só descobrir um por vez

f(5)= 5(ao quadrado) - 4 .5 - 2
f(5)= 25 - 18   f(5)=7

f(-2)= -2(ao quadrado) - 4.(-2) - 2
f(-2)= 4 + 4 - 2
 f(-2)= 6

Agora é só encaixar na equação
f(5) - 3.f(-2) = ?
7 - 3 . 6
7-18
-11

Prontinho.